Encounter of Religious East and Secular West: Moral Collisions - Музыкина, Елена (Eurasian Journal of Religious Studies, 2017)
Considering the contemporary socio-cultural situation in Western Europe prompted by the growth of migrants arriving there from Muslim Middle East countries, one can talk about a meeting of two opposing moral systems. The difference is primary manifested in the importance of religious factor for each system. Religion continues to be an integral component of the Islamic society, bonding and determining all the other components (social, legal and other systems), thus this characteristic is difficult to grasp for secular society in Western Europe. Moreover, Europeans often see the arrival of a new daily existence paradigm as a cultural expansion, infringement of their well-established way of life. Such a perception leads to conflicts witnessed worldwide. Yet there are some steps to be taken to overcome the tension, but they are a must for both side of the conflict.